Evaluating an ultrasound-guided peripheral intravenous cannulation training program for emergency clinicians: An Australian perspective. (September 2020) - Archer-Jones, Amy; Sweeny, Amy; Schults, Jessica A; Rickard, Claire M; Johnson, Laura; Gunter, Ashleigh; Watkins, Stuart
Abstract: Objective: The primary objective of this study was to identify the proportion of clinicians using ultrasound guidance (USG) to insert peripheral intravenous cannulas (PIVCs) in the emergency department (ED) following attendance at a hospital-based USG PIVC training program. Methods: Over 12-months, USG cannulation training sessions were offered to nurses and doctors competent in standard PIVC insertion (landmark technique), working in the ED. Surveys pre and post-training captured participants' self-reported confidence with cannulation and USG cannulation using a 5-point Likert scale. Supplemental data from observation periods before and after the trainings assessed departmental cannulation practices overall. Data were analysed using descriptive statistics and associations analysed using chi-square tests. Results: Overall, 195 participants attended training; 58% completed follow-up surveys. Forty-three percent reported using USG cannulation the following month. The median confidence score amongst workshop participants increased from 1 to 3 (p < .001). Post-implementation, use of USG cannulation increased from 0.7% to 6.0% post-training (p < .001), although the overall number of attempts at PIVC placement did not change. Conclusions: USG cannulation training increased this practice in the short-term. However, no significant difference in the number of attempts was observed. Further investigation in controlled settings is needed to inform the widespread implementation of USG cannulation training packages.